Acceptance of Electronic Health Records in Traditional Malay Medicine: An Exploratory Prototyping Approach - Raja Ikram, Raja Rina; Abd Ghani, Mohd Khanapi; Mohd Naim, Mohd Hariz; Idris, Ariff; Choon, Ngo Hea; Kanchymalay, Kasturi; Hasan Basari, Abd Samad; Ishak, Nadiah; Ab Hamid, Noor Raihan (International Journal of Integrated Engineering, 2021)
The usage of electronic health records is widely used today in the modern medicine field due to its immense benefits. These benefits include and are not limited to allowing physician to access a patient’s chart remotely, provide alerts to a potential medication error and critical lab values. However, the usage of this technology in Traditional Malay Medicine is limited. This paper explores the acceptance usage of electronic health records in Traditional Malay Medicine in five healthcare organisations including private Traditional Malay Medicine practitioners in Malaysia. This research utilizes the exploratory prototyping approach where a prototype, MyPostnatalSys is developed and used to gain constructive feedback of the acceptance of electronic health records. MyPostnatalSys, an electronic health record prototype, was developed for integrating Traditional Malay Medicine and Modern Medicine services using an interoperability standard, HL7. The purpose of interoperability standards is to ensure patient data can be transmitted across multi-platform systems seamlessly. The results show that more than 90% respondents have shown a positive acceptance on the usage of electronic health records in Traditional Malay Medicine. However, there may exist some resistance in accepting electronic health records technology in private Traditional Malay Medicine practitioners. However Traditional Malay practitioners trained by a government led initiative for women’s health, Mamacare programme, are more open to accept the implementation. This shows that upskilling programmes such as Mamacare can reduce the barriers of acceptance in electronic health records in Traditional Malay practitioners.